Productivity improvement in a company of the industry of bolting systems - Oliveira, Jorge Miguel Porfírio (2022)
Nowadays, the companies face an extreme need of having high levels of productivity (P) in order to survive in the market`s competition. In this context, this work was performed in the production department of alki Technik GmbH, a company that operates in the field of bolting systems, making production of tools in a make-to-order (MTO) basis, and services as well. The work had the main aims of measurement of the production performance in terms of its P level and establishment of strategies to reach its improvement. The first phase of the work was focused in obtaining the necessary elements to measure the real levels of P in a weekly basis, which are the inputs (IN) in terms of time capacity and the outputs (OUT) in terms of time with production of tools and execution of services. After found ways to properly quantify IN and OUT, the P started to be observed and after the first three weeks, the observed Ps were considered too low for what the company needs, and it was also confirmed when compared with P levels presented in another studies. Some improvement methods were implemented, such as, a Visual Management (VM) method, which consisted in establishing each Friday a map with a work plan for the following week and placing it in the workshop, and Kaizen philosophy in terms of asking the employees about activities of their daily work that they considered that could be optimized to proceed with its analysis as Kaizen Optimizations (KOs), in order to find optimization solutions. A total of six KOs were proposed, being the time saving estimate of 101 hours per year. One of the KOs was immediate implemented, as well as the VM method, and the following three weeks showed P improvement, with the observed indexes of 59,2%, 52,1% and 58,3% respectively, when on previous weeks the highest observed value had been 43,7%. Finally, it was made the analysis of the workshop`s layout, as facility layouts play also a huge role in the productive performance, through the Systematic Layout Planning (SLP) method in order optimize the flows. From this analysis, two optimization alternatives (OAs) were designed. OA1, where a few changes are proposed without extra costs have been estimated a cost reduction with flows of 5,94% OA2, where some further changes are proposed, being in this case the estimated costs reduction with flows of 20,3%. However, this last OA would carry costs of its implementation. The conclusions highlight the P improvement achieved through this work. Further improvement was left through the KOsfor the process and OAsfor the workshop layout.